Fetal structural anomaly screening at 11-14 weeks of gestation at Maharaj Nakorn Chiang Mai Hospital - Kasemsri Srisupundit (2018)
Objective: To determine the detection rate by ultrasound scanning of fetal anomaly by first trimester (11-14 weeks of gestation). Material and Method: A prospective descriptive study of 597 pregnant women undergoing Nuchal Translucency (NT) measurement at 11-14 weeks of gestation at Maharaj Nakorn Chiang Mai Hospital. The sonographic examinations focused on NT thickness and fetal structural survey. The final diagnoses were based on neonatal outcomes assessed by the pediatricians and abortuses evaluated by the pathologists. The main outcome measure was the detection rate of fetal anomaly using ultrasonographic examination. Results: Of 597 pregnant women recruited into the present study, the mean age was 29.41±5.8 years, the incidence of fetal anomaly was about 4% (24 from 597 cases). The detection rate by first ultrasound scans was 58% (14 from 24 cases) and the most common detected structural anomaly was cystic hygroma and exencephaly. The rate of undetected fetal anomalies was 42% (10 from 24 cases). Abnormal NT was found in 16 from a total of 597 cases (2.7%), most of them, however, had normal karyotype and no gross anomaly at birth. Conclusion: First trimester (11-14 weeks) ultrasound scan is probably a useful method for detection of fetal structural anomalies with a relatively high detection rate, and may be a good adjunct to the conventional examination.